Assessment of overweight, obesity and metabolic variables among students of a private medical college in Dhaka city (Bangladesh Journal of Medical Science, 2015)
Background: Overweight and obesity are recognized as recent threat which affecting both developing and developed countries. Obesity and its associated morbidities are leading cause of most non-communicable diseases. Few recent studies have indicated the presence of increase in overweight and obesity among children and adolescent but there is no study among adult groups. Method and material: This cross sectional study was done to assess the prevalence of overweight, obesity and metabolic variables with their relation among medical students. Result: Our result reveals that 8.6% & 1.9% male and 15% & 3.2% female are suffering from overweight and obesity (based on BMI) respectively. More females (31.3% and 65.2%) are centrally obese than males (3.5% and 34.8%) (According to Waist Hip ratio and Waist Height ratio respectively). But according to Waist circumference more males (30.7%) are obese than females (24%). There is also significant difference of male and female BP. DBP and SBP of male (79.22mmHg & 118.9 mmHg) have high normal level than female (72.71mmHg and 108.67mmHg) (P